Evaluasi Kebutuhan Nutrien dan Suplementasi Zinc untuk Calon Galur Ayam IPB-D2 Fase Pre-layer: Evaluation of Nutritional Requirements and Zinc Supplementation for IPB-D2 Prospective Chicken Lines in the Pre-Layer Phase - Fadhilah Dhani Santika Falah; Sumiati; Cece Sumantri; Dwi Margi Suci (Jurnal Ilmu Nutrisi dan Teknologi Pakan (Nutrition and Feed Technology Journal), 2022)
This study aimed to evaluate nutrient requirements and zinc supplementation for IPB D-2 pre-layer chicken line candidates on performance, blood profile, and blood malondialdehyde (MDA). This study used 200 of 16 weeks IPB-D2 chickens line candidates reared until 19 weeks of age (pre-layer phase). This study used a completely randomized design (CRD) with 2 treatments and 10 replications. The treatment rations were formulated to fill the chicken nutrient requirements according to Lohman (2020) without the addition of Zinc and with the addition of 120 ppm Zinc. The data were analyzed using the T test. The results showed that the ration supplemented with 120 ppm zinc did not significantly affect performance, but it was able to increase body weight uniformity. The 120-ppm Zinc supplementation significantly (p<0.05) decreased erythrocytes, however it tended to lower blood MDA. In conclusion, 120 ppm Zinc supplementation in the ration is sufficient to meet the nutrient requirement of IPB-D2 chicken line candidates in the pre-layer phase. Key words: IPB-D2 chicken line candidates, Zinc, performance, blood profile, MDA